Women's knowledge of and attitude towards disability in rural Nepal. (April 2013) - Simkhada, Padam P.; Shyangdan, Deepson; van Teijlingen, Edwin R.; Kadel, Santosh; Stephen, Jane; Gurung, Tara
<x xml:space="preserve">Abstract</x> Purpose: What is perceived to be a disability is both culturally specific and related to levels of development and modernity. This paper explores knowledge and attitudes towards people with disabilities among rural women in Nepal, one of the poorer countries in South Asia. Method: Four hundred and twelve married women of reproductive age (aged 15–49 years), from four villages in two different parts of Nepal, who had delivered a child within the last 24 months preceding the study, completed a standard questionnaire. Results: The majority of the participants only considered physical conditions that limit function of an individual and are visible to naked eyes, such as missing a leg or arm, to be disability. Attitudes towards people with disability were generally positive, for example most women believed that disabled people should have equal rights and should be allowed to sit on committees or get married. Most respondents thought that disability could result from: (i) accidents; (ii) medical conditions; or (iii) genetic inheritance. Fewer women thought that disability was caused by fate or bad spirits. Conclusions: There is need to educate the general population on disability, especially the invisible disabilities. There is also a need for further research on disability and its social impact.